Structural Analysis of the Lower Witwatersrand Supergroup in the Vredefort Dome, South Africa - Manzi, Shalene (University of the Witwatersrand, Johannesburg, 2025)
Hypervelocity impact craters are sites of exceptionally large, focused, energy release that results in extreme stresses, finite strains and strain rates in target crust. In particular, large impact structures are characterised by complex internal morphologies involving second- and third-order structures. The formation of second-order features, such as central uplifts are successfully reproduced by numerical models such as iSALE, which assume gross hydrodynamic behaviour of the crust, even if the reason for such behaviour is not fully understood. However, within central uplifts, field and petrographic studies show that strain is highly heterogeneous at all scales. This study examines brittle and ductile features in the 2.02 Ga Vredefort Dome, the largest and most deeply eroded central uplift on Earth. It focuses particularly on three areas close to the contact between the massive crystalline core and the basal parts of layered supracrustal sequence located between 20 km and 22 km from the centre of the Dome, where the lithologically-heterogenous lower West Rand Group of the Witwatersrand Supergroup is well exposed. Geometric analysis of shatter cones, branching (horsetail) fractures and a near-orthogonal pair of cm-spaced, so-called shatter cleavages shows some preferred centrosymmetry linking them to the shock wave within the first few seconds of impact. A 3D analysis of two large faults with individual slips of 400 - 500 m provides the first evidence of a conjugate pair of originally tangentially-striking normal faults attributed to collapse of the transient crater wall approximately 1 minute after impact. Structural analysis of large pseudotachylyte dykes and vein networks establishes that they formed by frictional melting related to these faults. Brittle-ductile folding with steep tangentially-striking axial planes and shallow-plunging hinges and wavelength of ~ 800 m and amplitude of ~ 100 m is linked to central uplift collapse between 3 and 4 minutes after impact, and is distinct from previously recognised radially-oriented constrictional folds that formed ~70-90 s after impact. This was followed by late-stage concentric and radial-conjugate normal faults with centre down slip attributed to central uplift collapse, which also contain significant pseudotachylyte volumes. The final stage involves the intrusion of the granophyre impact melt intrusion into tensional fractures. The evidence of multiple stages of faulting emphasises the need for more careful analysis of the fault patterns in the collar of the Dome. Although no bilateral symmetry was detected in fault and bedding strike patterns shown in published maps, future work establishing the 3D geometry and relative chronology of the faults is recommended before testing this aspect again. The cumulative field evidence indicates that second-order structures in the collar of the Vredefort Dome preserve a complex, multistage record of evolving strain that can be resolved into initial transient crater wall collapse, intermediate convergent and upward flow (constriction) related to central uplift rise and later divergent and downward flow (flattening) linked to its collapse, and that can be matched to the general stress-strain predictions of iSALE numerical modelling. This suggests that applying conventional structural mapping techniques to central uplifts in multi-ring impact structures can assist in understanding their highly dynamic evolution.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2025
Keywords: Vredefort Dome; Pseudotachylyte; Fault; Fold; Frictional melt; Shatter cones; Shatter cleavage; Numerical modeling; Leapfrog; Stress; Strain; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-15: Life on land